Deciphering of ADP‐induced, phosphotyrosine‐dependent signaling networks in human platelets by Src‐homology 2 region (SH2)‐profiling. Issue 6 (18th February 2013) - Schweigel, Hardy; Geiger, Jörg; Beck, Florian; Buhs, Sophia; Gerull, Helwe; Walter, Ulrich; Sickmann, Albert; Nollau, Peter; Zahedi, René; Sickmann, Albert
<x xml:space="preserve">Abstract</x> Tyrosine phosphorylation plays a central role in signal transduction controlling many important biological processes. In platelets, the activity of several signaling proteins is controlled by tyrosine phosphorylation ensuring proper platelet activation and aggregation essential for regulation of the delicate balance between bleeding and hemostasis. Here, we applied Src‐homology 2 region (SH2)‐profiling for deciphering of the phosphotyrosine state of human platelets activated by adenosine diphosphate (ADP). Applying a panel of 31 SH2‐domains, rapid and complex regulation of the phosphotyrosine state of platelets was observed after ADP stimulation. Specific inhibition of platelet P2Y receptors by synthetic drugs revealed a major role for the P2Y1 receptor in tyrosine phosphorylation. Concomitant activation of protein kinase A (PKA) abolished ADP‐induced tyrosine phosphorylation in a time and concentration‐dependent manner. Given the fact that PKA activity is negatively regulated by the P2Y12 receptor, our data provide evidence for a novel link of synergistic control of the state of tyrosine phosphorylation by both P2Y receptors. By SH2 domain pull down and MS/MS analysis, we identified distinct tyrosine phosphorylation sites in cell adhesion molecules, intracellular adapter proteins and phosphatases suggesting a major, functional role of tyrosine phosphorylation of theses candidate proteins in ADP‐dependent signaling in human platelets.